CORRELATION OF LIBRARIAN COMPETENCE AND DIGITAL-BASED LIBRARY MANAGEMENT - Sanusi, Hary Priatna; Gustini, Neng; Chaniago, Syifa Ayu Santika (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
The library's progress is very dependent on the quality of human resources. This article aims to describe the competence of librarians at Islamic religious universities throughout the city of Bandung, digital-based library management at Islamic religious universities throughout the city of Bandung, and the relationship between the competence of librarians and digital-based libraries management at Islamic Religious Colleges in the City of Bandung. The method used in this study is a descriptive correlational method using a quantitative approach. This study used a saturated sampling method were all 31 samples. From the results of the study, it was concluded that: (a) The competence of librarians is included in the excellent category because it is in the interval range of 2.60 – 3.39 with a value of 3.34 (enough category); (b) Digital-based library management is included in the good category because it is in the interval range of 2.60 – 3.39 with a value of 3.25 (enough category); and (c) The relationship between librarian competence and digital-based library management has a relationship of 0.796, with the coefficient value falling into the 0.06 - 0.799 category, which means that there is a strong relationship. In addition to the professional competence of librarians, to realize digital library management, they need technological literacy. The implementation of a digital library can be a means of supporting the progress of the quality of graduates in the global era.